History of vocational education and training in Europe : cases, concepts and challenges - Berner, Esther [Herausgeber]; Gonon, Philipp [Herausgeber] (Peter Lang, 2016)
Mit Beiträgen u. a. von WITTMANN (Vocational School Policy in Germany in the Context of Securing State Legitimacy), FLITNER (Policy for the Middle Classes vs. The Vichy Dictatorship. A Comparison of the Origins of State-Controlled Education for Workers in Germany and France), SCHÜTTE (Educational Systems Research: Intention, Scope, Desiderata. A Vocational-Pedagogy and Historical Comment), HAASLER (The German VET System and Labour Market Segregation by Gender: A historical Perspective), SANITER/TUTLYS (Comparison of Historical Development Pathways of Initial Vocational Education and Training in Lithuania and Germany: How Does History Matter for Policy Learning?), CLARKE/JANNSEN (Explaining Diverging VET Systems and Approaches in the Post-War Construction Sector: The Examples of Britain and the Federal Republic of Germany), SIECKE (Permeability in Two-Year Training Occupations in Germany: From Basic Training to Promotion of Lifelong Learning - a View at Historical and Current Developments). (BIBB-Doku)

"Understanding today's Vocational Education and Training (VET) systems requires a comprehension of the rise and development i.e. of the foundations of topical VET. This book is one of the first publications providing a comparative view of this development in Europe. Apart from other roots, the evolution of VET systems are one trigger of modernization of economy, society and education itself. The 28 contributions including countries like Austria, Britain, Denmark, Finland, France, Germany, Italy, Lithuania, Norway, Spain, Sweden and Switzerland of renowned authors and experts in this field are organized in three sections: 'Concepts' which are discussing theoretical approaches towards this phenomenon. 'Cases' which stress specific developments of VET in a certain country or region and 'Challenges' which are contextualizing the historical perspective in a topical policy context." (Publisher, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 2.3 Berufsbildungspolitik; T 1.2 Historische Berufsbildungsforschung; I 2.2 Europa; I 2.1 Deutschland; I 2.2.1 Westeuropa; Historische Berufsbildungsforschung; Berufsbildung; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Historische Entwicklung; Durchlässigkeit im Bildungssystem; Internationaler Vergleich; 19. Jahrhundert; 20. Jahrhundert; Europa; Bundesrepublik Deutschland; Schweiz; Österreich; Italien; Spanien; Schweden; Norwegen; Finnland; Frankreich; Großbritannien; Dänemark; Litauen